Your services will not be more necessary for the abc company - Ana Paula Pessotto; Rosiane Dutra Martins; Vitor Francisco Dalla Corte (Revista Brasileira de Ensino Superior, 2018)
The manager of the production area of the ABC Refrigerator, Marcos faced a great challenge, gaining trust and credibility of employees. Over time, established a friendly relationship with everyone, even charging goals and results, is seen by their employees as a fair and correct manager. In her first year of work Marcos had to fire Maria, after a period of sick leave, since she was no longer a productive worker. Because of this Maria decides to sue the company in justice, however her three children still work in the refrigerator and its attitude ends up putting Marcos in a dilemma, since the directors suggest that the manager dismisses the children of Maria, alleging that “birds of a feather”. Marcos knows that Maria’s children are great employees, productive and with excellent performance, but Marcos needs to resolve if he meets the suggestion of his superiors, firing or not John, Paul and Peter. In addition, Marcos was appointed as a witness to represent the company in the labor lawsuit filed by Maria, even though she knows that all the management practices mentioned in the judicial process are true, she will have to decide whether to testify in favor of the company or not. This teaching case aims to encourage reflection on management practices in the context of work, and can be used in undergraduate or specialization courses and in disciplines related to people management, organizational theories and ethics. Applies to discussions on scientific and psychodynamic work management.